THE EFFECT OF WORK CLIMATE AND MOTIVATION TOWARDS TEACHERS' PERFORMANCE IN TEACHING AND LEARNING PROCESS - Dian Tauchida (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Work climate and work motivation for teachers that affect their success in carrying out their profession to be investigated, to explore information and understand educational practices that have achievements and vice versa, the extent to which the work climate and teacher motivation also influence and even determine it. The purpose of this study was to determine whether the climate and work motivation either partially or simultaneously affect the performance of teachers in the teaching and learning process. This type of research is quantitative with multiple linear regression method. Data collection through: filling out questionnaires and interviews. Analysis of the data using SPSS media in the form of validity, reliability and hypothesis testing. This study resulted in the findings (1) The work climate has an effect on teacher performance in the teaching and learning process as indicated by the significance value of the work climate variable (X1) of 0.025 <0.05, it can be concluded that Ha is accepted and Ho is rejected. The tcount value of the work climate variable is 2,394 > ttable 2,069. This means that there is an effect of work climate (X1) on teacher performance (Y) in the teaching and learning process. (2) Motivation has an effect on teacher performance in the teaching and learning process by 0.007 <0.05 and through the t test, the t value for motivation is 2.992 > t table 2.069. So it can be concluded that Ha is accepted and Ho is rejected. (3) Work climate and motivation have a simultaneous effect on teacher performance in the teaching and learning process of 8.519 > Ftable 3.40 with a significance level of 0.002 < 0.05, it can be concluded that Ha is accepted, Ho is rejected.